A review of fatigue damage assessment in offshore wind turbine support structure. (November 2022) - Haselibozchaloee, Danial; Correia, José; Mendes, P.; de Jesus, Abilio; Berto, F.
Highlights: Nonlinear fatigue accumulation. Time- and frequency domains. Shape functions. Multiaxial fatigue. Abstract: According to the climate crisis, offshore wind turbines can play an important role to improve the green energy sector. Due to the rough and stochastic metocean environment, the fatigue existence in marine structures is inevitable. Several probabilities and artificial intelligence models can predict the metocean environment for fatigue assessment. Fatigue analysis can be done in time and frequency domains, and for enhancing the efficiency and speed of computation the hybrid model is proposed. Furthermore, the multivariate linear statistical models of the simplified fatigue are also fast with high accuracy. For the Fracture Mechanics method, the geometry functions would be very useful to approximate the fatigue crake growth rate. Besides, J-integral is a criterion to determine the orientation and along with of the fatigue crack and define the plastic behavior of the fatigue crack tip zone. In the local scale, UniGrow and SWT probability models could bring proper fatigue lifetime approximation and recognize the fatigue resistance and residual fatigue. Multiaxial fatigue also can consider the effect of the in- and out-of-phase loading effects through the critical plane method. Furthermore, a survey of the specific offshore steel shows that the fatigue lifetime does not have good agreement with the S-N curve of guidelines due to the inhomogeneity of the material and different mechanical properties. The PhyBal method was used to reduce the cost of the fatigue test and improve the fatigue approximation accuracy.